2023
DOI: 10.3389/fonc.2023.1076835
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term prehabilitation of older patients with colorectal cancer: A propensity score-matched analysis

Abstract: ObjectiveThe aim of this study was to assess the impact of short-term, hospital-based, supervised multimodal prehabilitation on elderly patients with colorectal cancer.MethodsA single-center, retrospective study was conducted from October 2020 to December 2021, which included a total of 587 CRC patients who were scheduled to undergo radical resection. A propensity score-matching analysis was performed to reduce selection bias. All patients were treated within a standardized enhanced recovery pathway, and patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This review specifically addresses recent evidence related to the economics and the cost effectiveness of surgical prehabilitation. The programs reported either a reduction in healthcare related costs [10,12,14,15] or no impact on them [9 ▪ ,13,16 ▪ ,17,18 ▪▪ ], except one study, which reported no increase in costs only in a subgroup of PG [11]. However, the current studies demonstrate a heterogeneity of the programs‘ structure and of the included population, as a recent systematic review of Rombey et al also debated [6].…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…This review specifically addresses recent evidence related to the economics and the cost effectiveness of surgical prehabilitation. The programs reported either a reduction in healthcare related costs [10,12,14,15] or no impact on them [9 ▪ ,13,16 ▪ ,17,18 ▪▪ ], except one study, which reported no increase in costs only in a subgroup of PG [11]. However, the current studies demonstrate a heterogeneity of the programs‘ structure and of the included population, as a recent systematic review of Rombey et al also debated [6].…”
Section: Discussionmentioning
confidence: 51%
“…The healthcare cost reduction was mainly achieved by reducing the length of hospitalization [4,10–12,14,16 ▪ ,17]. This would also allow the hospitals to have a higher patient turnover, thus, to generate more income.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations